Cutaneous presentation of metastatic pancreatic cancer. Issue 12 (28th December 2022) - Abdelaziz, Mohammed; Thorley, Daniel; Ahmed, Waseem
Abstract: Pancreatic cancer typically presents with a cholestatic picture of jaundice, bloating and bowel changes, secondary to the obstruction of the biliary system. In tail of pancreas metastases, this clinical presentation may be absent, meaning that the disease progression can be more insidious. Cutaneous spread in pancreatic malignancies is often iatrogenic due to direct spread from the tumour site during diagnostic sampling or surgery. Rarely, cutaneous spread can be noted at distant sites, which is associated with widespread disease dissemination and poor prognostic outcomes. Our case focusses on a patient who developed metastatic spread to the chin, as a first presentation, with no other significant associated symptoms identified.